Collusion and conspiracy in colonial Natal : a case study of Reynolds Bros and indentured abuses 1884-1908 (Historia, 2021)
The pronouncements of the Coolie Commission of 1872 against the ill-treatment of indentured labour in the Natal Colony and the subsequent appointment of a Protector of Indian Immigrants did not deter certain employers from exploiting those indentured to them. Over a period of almost 25 years reports of assaults, desertions, deaths and suicides emanated from the Reynolds sugar estates in the Umzinto district. Yet a veneer of indifference, which evolved into a conspiracy of silence on the part of officialdom and civil society, served to protect the image of Reynolds Bros from censure. Moreover, within the ranks of the "sugarocracy" profits were prioritised ahead of human rights. This state of affairs was facilitated by the prevailing inherent ethnocentrism of the period. Thanks to the persistence of James Polkinghorne, as the Protector of Indian Immigrants, the extent of the abuse of human rights by Reynolds Bros was eventually exposed and appropriate remedial action taken. Ten spyte van die uitsprake van die sogenaamde Coolie Commission van 1872 ten opsigte van die mishandeling van die inboekstelsel arbeiders in die Natalse Kolonie, asook die aanstelling van 'n Beskermer van Indiese Immigrante, het dit egter steeds nie sekere werkgewers daarvan weerhou om hulle ingeboekte arbeiders uit te buit nie. Oor 'n tydperk van bykans 25 jaar het berigte van aanrandings, drostery, sterftes en selfmoorde steeds voortgespruit uit die Reynolds suiker landgoed in die Umzinto distrik. Maar 'n skyn van onverskilligheid, wat mettertyd ontwikkel het in 'n sameswering van verswyging aan die kant van die amptenary asook die burgerlike samelewing, het egter gedien om die beeld van die Reynold broers te beskerm teen sensuur. Daarbenewens het winste voorrang geniet bo menseregte in die geledere van die "sugarocracy". Hierdie toedrag van sake was deur die heersende etnosentrisme van die tydperk vergemaklik. Danksy die volharding van James Polkinghorne, as Beskermer van die Indiese Immigrante, was die omvang van die skending van menseregte deur die Reynolds broers uiteindelik blootgestel en gevolglik was toepaslike regstellende aksie geneem.
Keywords: Umzinto; Inboekstelsel arbeiders; Suikerproduksie; Worker suicides; Reynolds; Wragg Commission